Google Scholar: Platforming the scholarly economy - Jake Goldenfein; Daniel Griffin (Internet Policy Review, 2022)
Google Scholar has become an important player in the scholarly economy. Whereas typical academic publishers sell bibliometrics, analytics and ranking products, Alphabet, through Google Scholar, provides "free" tools for academic search and scholarly evaluation that have made it central to academic practice. Leveraging political imperatives for open access publishing, Google Scholar has managed to intermediate data flows between researchers, research managers and repositories, and built its system of citation counting into a unit of value that coordinates the scholarly economy. At the same time, Google Scholar's user-friendly but opaque tools undermine certain academic norms, especially around academic autonomy and the academy's capacity to understand how it evaluates itself.
Keywords: 300; Digital platforms; Autonomy; Google; Bibliometrics; Platform economy